The Situation of Incommensurability in Strategic Management - Yassine Talaoui (Symphonya, 2023)
The field of strategic management has witnessed a proliferation of theoretical perspectives following two main paradigms. The two camps roughly correspond, on the one hand, to the "classical" and "neo-classical" approaches, and on the other to the "contingency", "post-classical" and "postmodern" approaches. Underpinning these two camps are different conceptions of the theory of the firm and the purpose of theory itself in understanding business strategy, which are difficult and perhaps impossible to reconcile. Against this backdrop, this paper seeks to expose the roots of this interminable argument over theory and proposes a way to escape this situation of incommensurability.